P272 Tofacitinib as salvage therapy for patients hospitalized with refractory severe active ulcerative colitis: a GETAID multicenter prospective/retrospective cohort. (27th May 2021) - Uzzan, M; Bresteau, C; Laharie, D; Stefanescu, C; Carbonnel, F; Serrero, M; Viennot, S; Nachury, M; Amiot, A; Altwegg, R; Picon, L; Nahon, S; et al.
Abstract: Background: Up to 25% of patients with ulcerative colitis (UC) will require hospitalization for severe flare. In UC patients admitted who have already experienced multiple drug failures, including steroids and anti-TNF agents, new quick-acting medical options are needed. Tofacitinib is effective in refractory UC and has a rapid mechanism of action. It could be considered in this setting. We aimed to evaluate the efficacy and safety of tofacitinib in patients hospitalized for an acute UC flare. Methods: We conducted an observational and multicenter study with both retrospective and prospective collections in 14 GETAID tertiary IBD centers. The primary objective was to assess the survival without colectomy following tofacitinib initiation. We determined rates of clinical response, clinical remission, and clinical steroid-free remission at week 6 and week 14 and safety. Results: Fifty-eight patients were included. All but one patient with active lupus were exposed to antiTNF. 50 (86.2%) patients have received infliximab and 18 (31%) to ciclosporin. Patients were previously exposed to a median of 2.5 lines of biologic treatment before tofacitinib.Median Lichtiger at inclusion was 11.5 (interquartile range IQR[9 - 13]), median CRP was 17 mg/l (IQR[6.5 - 67]) and total Mayo score was 10 (IQR[9.3 - 11]). Deep ulcerations were observed in 10 patients (17.2%).With a median follow-up of 6.5 months (IQR [2.9-12.4]), colectomy-free survival rates were estimated at 80.1% (95CI [70.1-91.4]) at 3 months and at 75.1% (95CI[64.1-88.1]) at 6 months. Rates of clinical response, clinical remission and clinical steroid-free remission were 60.3%, 46.6% and 37.9% at week 6 an, 48.1%, 37% and 35.2% at week 14, respectively. At the end of follow-up, 29 patients (50%) were still treated with tofacitinib. The survival without tofacitinib discontinuation was estimated at 82.8% (95CI[73.6-93.1), 67.8% (95CI[56.6-81.4]) and 46.2% (95CI[34.2-62.4]) at 1, 3, and 6 months (Figure 3).Regarding safety, no death was observed, three patients withdrew tofacitinib due to adverse events. Two herpes zosters occurred in patients aged over 60 years old. No thrombotic event occurred. Conclusion: Tofacitinib appears as a promising option in patients hospitalized with a severe UC flare that needs further validation in prospective and controlled trials.